(untitled) (British Journal of Global Ecology and Sustainable Development, 2025)
The article analyzes the mechanisms of interaction between credit policy and financial inclusion. Opportunities for access to credit resources will be studied for various segments of the population - small businesses, rural residents, youth, women, and low-income families. The influence of interest rates, collateral requirements, microcredit programs, and government guarantees in credit policy on the level of financial inclusion is thoroughly analyzed. The importance of the development of digital financial services and increasing financial literacy is also highlighted, and proposals have been developed.